Don't Forget to Play: Examining what Play looks like in Museums for Adult Visitors - Robinson, Maria (My University, 2016)
While play in museums for children is not a new concept, there is little research on what play looks like for the adult visitor. This study investigates adult play in museum exhibits designed for family learning, using Stuart Brown’s (2010) typology of play. Thirty visitors were observed between five exhibits at the City Museum, St. Louis MO and Science World, Vancouver B.C. Results showed that adults do play in these exhibits, and that they engage in various types of play, typically favoring body/movement play. These findings can be used by museums to understand how to create active opportunities to fully engage adult visitors.
Thesis (Master's)--University of Washington, 2016-06
Keywords: Adult; Museum Exhibits; Play; Six types of Play; Museum studies; museology